PERSPEKTIF SOSIOLOGIS TENTANG KEMANDIRIAN NAGARI DI SUMATERA BARAT MELALUI PENERAPAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 - Eriyanti, Fitri (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2015)
The passage of Village Act No. 6 2014 spurs pros and cons among the community of West Sumatera. Some see the act as the chance to re-implement â€œnagariâ€ system (a traditional village administration in Minangkabau community who lives in West Sumatera); others view it as an encouragement to separate from the Republic of Indonesia. However, this act is a product of the nationâ€™s law, and elaborated in The Indonesian Government Regulation No. 47 2015 about the Change of Government Regulation No. 43 2014 about the Regulation on Implementation of Village Act No.6 2014, which says that it has to be implemented and obeyed nationwide. The implementation causes opportunities and challenges to the traditional village. Traditional village, called â€˜nagariâ€™ in West Sumatera, is recognized as legal community based on its traditional and historical rights. This means West Sumateraâ€™s nagari is recognized autonomically after the passage of the Village Act No. 6 2014. This article deliberates the discourse on implementation of the Village Act to improve the nagariâ€™s autonomy in West Sumatera from the sociological perspective.